Pengaruh Komitmen Profesional, Self Efficacy, dan Intensitas Moral Terhadap Niat Untuk Melakukan Whistleblowing - Putra, Dwipa Darma; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2017)
The auditor's profession is in the spotlight of many parties related to a number of major corporate financial scandals that occur much in the latter. Therefore, the importance of whistleblowing is done to minimize fraud within the company. Factors influencing the auditor's actions to conduct whistleblowing are professional commitment, self efficacy, and moral intensity. The purpose of this study was to determine the effect of professional commitment, self efficacy, and moral intensity to the intention to conduct whistleblowing. The research was conducted at Public Accounting Firm (PAF) in Bali Province registered in the Directory published by Indonesian Institute of Certified Public Accountants (IICPAI) in 2016 which are all located in Denpasar City. Sampling method used in this research is purposive sampling method, while data collection method used in this research is by using questionnaire. The number of research samples used were 34 respondents. Data analysis technique used in this research is multiple linear regression analysis technique. Based on the result of the analysis, it can be found that professional commitment has a positive effect on the intention to conduct whistleblowing, self efficacy have positive effect on the intention to conduct whistleblowing and moral intensity have positive effect on the intention to conduct whistleblowing. This means that the better the professional commitment, self efficacy, and moral intensity the higher the auditor's intention to conduct whistleblowing.